Study on the restraint control of an isolation pile on an existing high-speed railway during the close passing of a shield machine - Tao, Yang; Shuailei, Liu; Hao, Zhao; Xingru, Li (Frontiers in Earth Science, 2023)
The impact of shield construction on the close lateral passing of high-speed railways can threaten the safety of operating high-speed railways. To study the deformation characteristics of the shield structure after the application of isolation piles from the ground surface and the deformation characteristics of the bridge piers of an overpassing high-speed railway, we analyze the mechanism of isolation pile restraint control and establish a three-dimensional numerical model of a shield structure to study the situation of a high-speed railway with a metro interval under passing a high-speed railway passenger line project. Combined with the measured data and numerical simulation data of the same construction stage, we study the impact of shield structure lateral passing on high-speed railway piers and surrounding ground surface in terms of the disturbance changes and the effect of isolation, as well as the effect of the lateral passing of the shield tunnel on the surface of the bridge piers and the surrounding area and the control effect of the isolation piles on the deformation. The results show that the isolation pile can block the development of the soil layer rupture surface and the stress path. The isolation pile has a good control effect on the vertical displacement of the bridge pier. The vertical displacement of the bridge pier decreases from 0.6 mm to 1.1 mm after the single- and double-track tunneling, and the displacement changes along the depth direction from nonuniform to relatively uniform. The vertical displacement of the ground surface includes both uplift and settlement, which occur at the same time. When the shield tunneling advances, the form of the ground settlement trough is changed from a "V" shape formed by the right single-track tunneling to a "W" shape after the double-track tunneling. The isolation pile can effectively control the influence range of tunnel excavation; its lateral displacement form changes regularly, and the lateral uplift is always in a "double-C outward expansion" shape. The initial excavation greatly disturbs the initial stress field, so it is necessary to pay attention to the control and management of measures to destroy the initial stress field.